Analisis Potensi Pengembangan Sentra Industri Kreatif Di Surakarta: Studi Kasus Kelurahan Serengan - Aurelia, Jovina Chandra; Astuti, Winny; Permana, Chrisna T. (Jurnal Perencanaan dan Pengembangan Kebijakan, 2025)
A creative city aims to improve community welfare by nurturing local creative clusters. Surakarta is a creative city that developed by establishing creative clusters in the form of creative villages. It is widely known for its batik idustry. While most of its clusters focus on batik industries, Serengan Subdistrict has an alternative creative cluster potential that specifically produces blangkon and shuttlecock. This study employs a qualitative descriptive method to examine the potential of non-batik creative cluster in Serengan Subdistrict. Our analysis is guided by the three dimensions of creative potential: creative economy, creative milieu, and creative class. Data and information were collected from documentary reviews, observations, and interviews. The data were subsequently processed using a descriptive qualitative research method. The study findings emphasies the strong potential of Serengan to be promoted as a strategic creative cluster that produces alternative products amidst the domination of batik industries in Surakarta, which is expected to improve the well-being of the local community. However, among the three components of a creative city, the creative class and the creative milieu’s development remain underdeveloped. Collaborative processes and participatory activites are still infrequent, and there are no dedicated spaces that facilitate these interaction.